2020
DOI: 10.2147/ijgm.s260579
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychometric Evaluation of Persian Version of Nurses’ Intention to Care Scale (P-NICS) for Patients with COVID-19</p>

Abstract: Background: Given the high incidence of coronavirus and the shortage of nurses in Iranian hospitals, nurses' intention to care for patients with COVID-19 is important. The aim of this study is to evaluate the reliability and validity of the Persian version of the nurses' intention to care scale (NICS) by Iranian nurses who care for patients with COVID-19 in hospitals. Methods: A cross-sectional study was conducted on nurses (n= 400) at public and private Mazandaran hospitals. An online questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Self-efficacy, prior training, and information on the transmission of COVID-19, concerning about spread-ing disease to family, belief in a duty of care, the perceived value of one's response and empathy for patients affect nurses' intentions and willingness to work during epidemics and disasters [24][25][26][27][28]. Therefore, it is vital to understand nurses motivations for willingness to provide nursing care during a pandemic to inform current epidemic planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy, prior training, and information on the transmission of COVID-19, concerning about spread-ing disease to family, belief in a duty of care, the perceived value of one's response and empathy for patients affect nurses' intentions and willingness to work during epidemics and disasters [24][25][26][27][28]. Therefore, it is vital to understand nurses motivations for willingness to provide nursing care during a pandemic to inform current epidemic planning.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted during the MERS outbreak in Saudi Arabia, receiving financial benefits lowered their stress and encouraged their intention to work in a future pandemic [32]. Providing extra bonus can decrease nurses negative attitudes toward caring for patients with COVID-19 and increase nursing intention [26]. However, some other studies have reported opposite results wherein no difference was reported between willingness of nurses to provide nursing care and demographic variables in H1N1 influenza and COVID-19 [28,50].…”
Section: Discussionmentioning
confidence: 99%
“… Demographic information includes age, gender, marital status, years of work experience and education level (bachelor's or master's degree). Intention to care was measured using Persian version of Nurses’ Intention to Care Scale (P‐NICS) for Patients with COVID‐19. It consisted of 31 items and six domains: positive behavioural beliefs, negative behavioural beliefs, family subjective norms, work subjective norms, positive control beliefs and negative control beliefs (Rahmatpour et al, 2020). An intention to care variable was computed from the six subscales.…”
Section: Methodsmentioning
confidence: 99%
“…The Iranian healthcare system is struggling with challenges such as a shortage of nursing staff, migration of educated nurses to developed countries, nurses’ turnover, and pressure of imposed sanctions by the United States (2020; Shamsi & Peyravi, 2020; Sharif Nia et al, 2021; Shojaeimotlagh et al, 2018). Undoubtedly, one of the most important factors in the reduction of the number of Iranian nurses is the issue of their job satisfaction.…”
Section: Introductionmentioning
confidence: 99%